Toe-of-slope facies of the Eocene limestones in Aghioi Pantes sequence (Zakynthos island, Western Greece) - ΚΑΤΗ Μ. (Bulletin of the Geological Society of Greece, 2018)
The facies analysis of the Eocene limestones in the Aghioi Pantes section in central Zakynthos, part of the Preapulian carbonate sequence in the greater area, showed three megafacies types: a) graded beds, in which two main subtypes have been recognized, medium- to thin-bedded calcarenites-calcilutites and thick-bedded ruditic calcarenites, consisting mainly of redeposited shallow-water carbonate sands (mostly bioclasts of nummulites and echinoids); based on their sedimentary structures they have been interpreted as low density turbidite and high density turbidite (or sandy debris flows) deposits correspondingly, b) calcareous conglomerates consisting of shallow-water facies lithoclasts and abundant pelagic intraclasts all of which have been interpreted as debris flow deposits and c) folded strata of pelagic-hemipelagic composition that have been interpreted as slumps. Subsequently, the studied limestones constitute exclusively deep-water resedimented facies having been deposited mainly through sediment gravity flows, carrying significant amounts of shallow-water bio- lithoclastic material. The distribution and the organization of this facies association, with the dominance in particular of the base cut-out turbidites, suggest as depositional environment of the studied Eocene limestones a "low" in the outer slope connecting the Preapulian platform with the adjacent Ionian basin.